Influence of annealing temperature on microstructure and luminescent properties of Y2O3: Eu3+ deposited quartz fibre. (2nd January 2016) - Chen, Z. M.; Jiang, S. X.; Guo, R. H.; Xin, B. J.; Miao, D. G.
Abstract : In this study, Eu 3+ doped Y2 O3 (Y2 O3 : Eu 3+ ) phosphor target was deposited on quartz fibre substrates by electron beam evaporation technology, and then the deposited fibres were annealed at different temperatures from 600 to 1000°C. Particle shape was changed, and particle size of Y2 O3 : Eu 3+ was increased with the rise in annealing temperature. Crystallisation and luminescent intensity of the deposited films on quartz fibres were significantly improved by annealing treatment. The most effective crystallisation and the maximum luminescent efficiency of the thin films were obtained when the deposited fibres were treated at 1000°C for 1 h. The luminescent property results indicated that the particle shape, particle size and crystallisation were the important factors affecting luminescent intensity of the deposited fibres.